Parametric Study on the Connection Between Poisson’s Ratio, GSI and Environmental Stress - Lógó, Benedek András; Vásárhelyi, Balázs (Computer Assisted Methods in Engineering and Science, 2020)
According to its definition, Poisson’s ratio is a measure of the Poisson effect, the phenomenon in which a material tends to expand in directions perpendicular to the direction of compression or, in other words, Poisson’s ratio is the ratio of relative contraction to relative expansion. For the sake of simplicity, it is handled as a constant. However, in reality, it is a variable. One can find several studies on this topic. This paper aims to study the impact of the environmental (confining) pressure and rock quality (namely the geological strength index, GSI) of rock mass on Poisson’s ratio. By using parametric investigation, several cases were calculated to present the functional dependency between the quantities mentioned above.